Principles of Ecosystem Stewardship Resilience-Based Natural Resource Management in a Changing World - Folke, Carl.; Kofinas, Gary P.; Chapin, F. Stuart; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2009)
Natural resource management is entering a new era in which rapid environmental and social changes inevitably alter ecosystems and the benefits they provide to society. This textbook provides a new framework for natural resource management$1 (Ba framework based on stewardship of ecosystems for ecological integrity and human well-being in a world dominated by uncertainty and change. The goal of ecosystem stewardship is to respond to and shape changes in social-ecological systems in order to sustain the supply and availability of ecosystem services by society. The book links recent advances in the theory of resilience, sustainability, and vulnerability with practical issues of ecosystem management and governance. Chapters by leading experts then illustrate these principles in major social-ecological systems of the world. Inclusion of review questions, glossary, and suggestions for additional reading makes Principles of Ecosystem Stewardship: Resilience-Based Natural Resource Management in a Changing World particularly suitable for use in all courses of resource management, resource ecology, sustainability science, and the human dimensions of global change. Professional resource managers, policy makers, leaders of NGOs, and researchers will find this novel synthesis a valuable tool in developing strategies for a more sustainable planet. About the Authors: F. Stuart Chapin, III is Professor of Ecology in the Institute of Arctic Biology, University of Alaska Fairbanks. Gary P. Kofinas is Associate Professor of Resource Policy and Management in the School of Natural Resources and Agricultural Sciences, University of Alaska Fairbanks. Carl Folke is Professor and Science Director of the Stockholm Resilience Centre, Stockholm University.s
Conceptual Framework -- A Framework for Understanding Change -- Managing Ecosystems Sustainably: The Key Role of Resilience -- Livelihoods and Human Well-Being during Social-Ecological Change -- Adaptive Co-management in Social-Ecological Governance -- Transformations in Ecosystem Stewardship -- Stewarding Ecosystems for Society -- Conservation, Community, and Livelihoods: Sustaining, Renewing, and Adapting Cultural Connections to the Land -- Forest Systems: Living with Long-Term Change -- Drylands: Coping with Uncertainty, Thresholds, and Changes in State -- Freshwaters: Managing Across Scales in Space and Time -- Oceans and Estuaries: Managing the Commons -- Coastal Marine Systems: Conserving Fish and Sustaining Community Livelihoods with Co-management -- Managing Food Production Systems for Resilience -- Managing Densely Settled Social-Ecological Systems -- The Earth System: Sustaining Planetary Life-Support Systems -- Integration and Synthesis -- Resilience-Based Stewardship: Strategies for Navigating Sustainable Pathways in a Changing World.
Keywords: Environment; Ecosystems; Environmental law; Environmental policy; Environmental management; Geoecology; Environmental geology; Ecotoxicology; Nature conservation; Environment; Nature Conservation; Environmental Management; Ecotoxicology; Ecosystems; Environmental Law/Policy/Ecojustice.; Geoecology/Natural Processes; Electronic books